One Bite, Two Severe Envenomations Despite Antivenom Therapy: A Case Report - Ravi Shukla; Puja Shrestha; Binod Khanal; Shraddha Paudyal; Bipal Regmi (Clinical Case Reports, 2025)
ABSTRACT This case report describes a 12‐year‐old child who was bitten by a cobra and developed two distinct systemic neurotoxic episodes, 19 h apart, along with severe local envenoming, despite receiving appropriate treatment with antivenom and making a full recovery. It also highlights the use of neostigmine for severe symptoms and emphasizes the importance of prompt wound care to prevent long‐term complications. A potentially life‐ and limb‐threatening event was successfully avoided through an inter‐departmental approach.